2004
DOI: 10.2190/je7w-vl6w-rnyf-rd4m
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Metacognitive Skills on Learners' Memory of Information in a Hypermedia Environment

Abstract: Twenty-eight students (aged 9 to 17) freely explored a science Web site structured either in an outline (linear) format or "puzzle" (non-linear) format for 2.5 hours. Subjects then engaged in tasks involving locational memory and informational recall. The results indicate that presence of metacognitive skills was a necessary but not sufficient condition for learning in hypermedia environments; the navigational structure of the Web site also was important. Metacognitive skill (as measured by the Junior Metacogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 25 publications
1
30
0
1
Order By: Relevance
“…"Hypermedia browsers must be able to monitor their own comprehension of the information presented in hypermedia, select appropriate strategies for correcting any misconceptions, and develop information seeking strategies that facilitate integrating information and synthesizing information from the hypermedia" (Jonassen and Grabinger 1990, p. 20). Accordingly, it has been suggested that learners who are better able to cope with these demands, because they possess self-regulatory skills, benefit more from hypermedia learning than students who lack the respective skills (Azevedo 2005;Bendixen and Hartley 2003;Hartley 2001;Schwartz et al 2004;Young 1996). Azevedo (2005) claims that if "learners do not regulate their learning when using hypermedia environments we may erroneously conclude that the environments are inherently ineffective, when in fact what is needed is to foster students' self-regulation while using these powerful but complex learning environments" (p. 203).…”
Section: Self-regulatory Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…"Hypermedia browsers must be able to monitor their own comprehension of the information presented in hypermedia, select appropriate strategies for correcting any misconceptions, and develop information seeking strategies that facilitate integrating information and synthesizing information from the hypermedia" (Jonassen and Grabinger 1990, p. 20). Accordingly, it has been suggested that learners who are better able to cope with these demands, because they possess self-regulatory skills, benefit more from hypermedia learning than students who lack the respective skills (Azevedo 2005;Bendixen and Hartley 2003;Hartley 2001;Schwartz et al 2004;Young 1996). Azevedo (2005) claims that if "learners do not regulate their learning when using hypermedia environments we may erroneously conclude that the environments are inherently ineffective, when in fact what is needed is to foster students' self-regulation while using these powerful but complex learning environments" (p. 203).…”
Section: Self-regulatory Skillsmentioning
confidence: 99%
“…Under learner control, learners with low levels of selfregulated learning strategies showed poorer performance than those with better skills, while there were no respective differences under system control. Schwartz et al (2004) demonstrated that metacognition predicted learning outcomes within a hypermedia environment only if this environment required an active metacognitive knowledge to construct meaning within the unfamiliar structure. Thus, they suggested that metacognitive skills are a necessary, but not a sufficient condition for learning in a hypermedia environment; rather, the structure of hypermedia (i.e., whether it requires a high degree of self-regulation or not) also matters.…”
Section: Self-regulatory Skillsmentioning
confidence: 99%
“…However, because the Internet allows for greater independence and for individual differences to influence how the technology is used, it also requires more in terms of learners' self-regulation. Accordingly, Schwartz et al (2004) found that selfregulatory skills predicted students' learning from hypertext, and Azevedo and Cromley (2004) found that students assigned to a training session in self-regulated learning outperformed students in a control condition when studying the circulatory system in a hypermedia environment. In open-ended digital learning environments, self-regulatory skills are probably necessary to search for and integrate information from various sources (Rouet 2006), as well as to avoid distractions represented by trivia and seductive details (Meyer and Rose 1998).…”
Section: Self-regulation and Computer-based Learningmentioning
confidence: 99%
“…Although the benefits of self-regulated activities seem obvious (Hartley 2001;Schwartz et al 2004), many students do not spontaneously use them, even at a university level (Busato et al 1998). According to Pintrich and Zusho (2002), many college and older students fail to develop cognitive and motivational strategies for regulating their learning.…”
Section: Introductionmentioning
confidence: 99%